Laboratory and On-sky Validation of the Shaped Pupil Coronagraph's Sensitivity to Low-order Aberrations With Active Wavefront Control. (13th March 2018) - Currie, Thayne; Kasdin, N. Jeremy; Groff, Tyler D.; Lozi, Julien; Jovanovic, Nemanja; Guyon, Olivier; Brandt, Timothy; Martinache, Frantz; Chilcote, Jeffrey; Skaf, Nour; Kuhn, Jonas; Pathak, Prashant; et al.
Abstract: We present early laboratory simulations and extensive on-sky tests validating of the performance of a shaped pupil coronagraph (SPC) behind an extreme-AO corrected beam of the Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) system. In tests with the SCExAO internal source/wavefront error simulator, the normalized intensity profile for the SPC degrades more slowly than for the Lyot coronagraph as low-order aberrations reduce the Strehl ratio from extremely high values (S.R. ∼ 0.93–0.99) to those characteristic of current ground-based extreme AO systems (S.R. ∼ 0.74–0.93) and then slightly lower values down to S.R. ∼ 0.57. On-sky SCExAO data taken with the SPC and other coronagraphs for brown dwarf/planet-hosting stars HD 1160 and HR 8799 provide further evidence for the SPC's robustness to low-order aberrations. From H-band Strehl ratios of 80% to 70%, the Lyot coronagraph's performance versus that of the SPC may degrade even faster on sky than is seen in our internal source simulations. The 5- σ contrast also degrades faster (by a factor of two) for the Lyot than the SPC. The SPC we use was designed as a technology demonstrator only, with a contrast floor, throughput, and outer working angle poorly matched for SCExAO's current AO performance and poorly tuned for imaging the HR 8799 planets. Nevertheless, we detect HR 8799 cde with SCExAO/CHARIS using the SPC in broadband mode, where the S/N for planet e is within 30% of that obtained using the vortex coronagraph. The shaped-pupil coronagraph is a promising design demonstrated to be robust in the presence of low-order aberrations and may be well-suited for future ground and space-based direct imaging observations, especially those focused on follow-up exoplanet characterization and technology demonstration of deep contrast within well-defined regions of the image plane.